Pengaruh Lingkungan, Disiplin, Dan Kepuasan Terhadap Kinerja Pegawai Pada Kantor Perum KPH Perhutani Kota Probolinggo - Wibowo, Satriyo; Hudzafidah, Khusnik; Pujiastuti, Agustina (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
Human resources (HR) provide great potential for driving factors supporting company activities which must be utilized as best as possible through synergy with the environment. The performance of employees supports the company's success in achieving its goals on an ongoing basis. The type of research used is an associative quantitative approach. The sampling technique used was a saturated sampling technique, the sample in this study was all employees of Perum KPH Perhutani Kota Probolinggo, totaling 73 people. The data sources used come from primary data and secondary data. Data was collected using a questionnaire and processed using data analysis methods in the form of validity tests, reliability tests, classical assumption tests, multiple regression analysis, coefficient of determination (R Square) and hypothesis testing. The research results show that there is an influence between the Work Environment (X1), Work Discipline (X2) and Job Satisfaction (X3) which simultaneously have a significant effect on Employee Performance (Y) where the Fcount value = 22.310. Then, the partial test shows that the Work Environment variable (X1) has a significant effect on Employee Performance (Y) with a tcount = 6.169 and Discipline (X2) partially has a significant effect on Employee Performance (Y) with a tcount = 5.870. Then, the partial test shows that the Job Satisfaction variable (X3) has a significant effect on Employee Performance (Y) with a t value = 2.683. In the results of the study, the dominant influence of the Work Environment variable (X1) has a dominant influence on Employee Performance (Y). Keywords: Work Environment, Discipline, Job Satisfaction, Employee Performance.